(3RHO GdQbGFb aj MSGH GdOQL hGdObGFbs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3gPg ebOeg SgdI Ef TGA Gddg JYGdi ai MSGH GdfSHI GdSJjJjI GNJUQJgG ef ebOeJi GdeSeGg HQbGFb GdMbGFb hSejJgG RjO GdQbGFb s
(3BNQgG (B:s
(3Ef cfJ CNPJ GdRGFO jMUd GdeWdhH hai Pdc caGjI def hab s
(3Vef eLehY , JQJjHgG (B: (3ef U (B188 - (3U(B206s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B168 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B61 s
Keywords: (3Gdadcs